2012
DOI: 10.1371/journal.pone.0050371
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multiple Phototransduction Pathways in a Reef-Building Coral

Abstract: Photosensitive behaviors and circadian rhythms are well documented in reef-building corals and their larvae, but the mechanisms responsible for photoreception have not been described in these organisms. Here we report the cloning, immunolocalization, and partial biochemical characterization of three opsins and four G proteins expressed in planulae of the Caribbean elkhorn coral, Acropora palmata. All three opsins (acropsins 1–3) possess conserved seven-pass transmembrane structure, and localize to distinct reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 44 publications
2
59
1
Order By: Relevance
“…Our data and data from other studies3960 show that Cnidarian intron-less opsins might have been derived from an ancient eumetazoan ciliary-like opsin containing introns by retro-transposition. Once anchored in the genome the ancient cnidopsin gene underwent several rounds of duplication, diversification and sensitivity tuning.…”
Section: Figuresupporting
confidence: 72%
See 2 more Smart Citations
“…Our data and data from other studies3960 show that Cnidarian intron-less opsins might have been derived from an ancient eumetazoan ciliary-like opsin containing introns by retro-transposition. Once anchored in the genome the ancient cnidopsin gene underwent several rounds of duplication, diversification and sensitivity tuning.…”
Section: Figuresupporting
confidence: 72%
“…However, we were unable to obtain any light-mediated activation of signal transduction via this pathway for Tc-group 1 opsins. We propose that opsins that did not signal in our assay either use different G-protein pathways, as recently proposed in reef corals60, act as photoisomerases or for unknown reason do not signal in our cell-line based assay, but nonetheless use Gs signaling cascade under natural conditions. The later possibility is, however, in our opinion very unlikely, because we saw comparable expression of all Tcops on the cell membranes of our test cell system and moreover not even a repeated flash stimulation lead to any response.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the case of Feuda et al (2012) data set, all the ctenophoran opsins identified by Schnitzler et al (2012) and the cnidarian opsins identified by Mason et al (2012) in the acroporan A . palmata were added to the alignment (generating FEAm1).…”
Section: Methodsmentioning
confidence: 99%
“…Because spawning is cued by lunar and daily changes in light intensity and spectral quality, it has been suggested that cryptochromes are involved in this process (Hoadley, Szmant, & Pyott, ; Levy et al., ; Reitzel, Tarrant, & Levy, ). Similarly, red‐photosensitivity has been documented in coral larvae, and three coral opsins (acropsin 1–3) homologous to human rhodopsins have been characterized in the coral Acropora palmata, suggesting that light detection associated with multiple behaviours in corals may be the result of a rhodopsin‐based visual system (Mason & Cohen, ; Mason et al., ). In addition, calcium has been described as a mediator of light responsivity in corals, and empirical evidence has shown that changes in [Ca 2+ ], brought on by shifts from day to night, control the time of broadcast spawning (Hilton, Brady, Spaho, & Vize, ).…”
Section: Introductionmentioning
confidence: 94%